IMPLEMENTASI APLIKASI PEMESANAN MAKANAN SERVICE DAN RESERVASI BERBASIS WEB PADA RESTORAN EKA RIA - Elis Sondang Dasawati, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2017)
Increasingly Evolving her a restaurant, the greater the data that must be processed to be accurate information manual processing has many problems few examples of cases when an employee or any admin convey information about the order list. menu prices were not reasonable because it is too expensive if it happens then the restaurants need to spend money to print the list menu again and be a waste of capital. Seeing an issue with such problems researchers offered a WEB-based application implementation to process the booking, price information, promotions, reservations and sales reports. This application is made with programming language PHP Hypertext Prepocessor ", which is a programming language that is widely used for handling the manufacture and development of a website and can be used in conjunction with HTML. Jquery collection javascript library simplifies Javascript code by calling the functions provided by jquery . Javascript itself is a scripting language that works side Client / Browser so that websites can be more interactive text editor used to implementation this is Aptana studio3.1. The collection of information is done with indirect observation methods and interview with a restaurant employee Eka Ria.untuk implementation method using this app has many features to support activity in the restaurant eka- ria As a menu to order food, bill printing, information relating to the reservation sperti information package info leases for prediction of total rental price of the room with the package and manufacturing sales report. Results from this study is a food ordering application, reservation service and transactions can be easy for customers to mendpatkan food menu and pricing information, and simplify admin of booking meals to get information about sales reports. The conclusion of this study is the application that can be easier to get the information menu, ordering food, making auto sales reports and reservations  Keywords: booking seafood, sales reports, WEB reservation